Development of Memorizing Surah Al-Ma'un Learning for Seven Year Old Children - Nurchari, Muadz Rasyid; Fiddarain, Zaduna; Nurrohim, Ahmad (Universitas Muhammadiyah Surakarta, 2023)
Quran education in early childhood is an integral part of an achievement that has the aim of developing potential in children. In an effort to increase the effectiveness of Quran learning, innovative game-based approaches have been introduced, one of which is through puzzle-based games. The author tries to analyze the strategies applied in integrating game technology into the context of Quran learning. Qualitative research seems sufficient to be able to identify the increase in children's participation and learning outcomes in memorizing the Quran. Hopefully, the existence of puzzle-based game learning technology can develop as well as increase children's motivation and concentration during the Quran memorization process.